The role of ultrasound in fetal congenital myopathy detection: a novel case of fetal‐onset cap myopathy. (21st July 2013) - Tamblyn, J. A.; Morris, R. K.; Cox, P.; Hargitai, B.; Kilby, M. D.
Abstract : What's already known about this topic? Rare heterogeneous group of neuromuscular disorders. Associated with severe, often fatal phenotypes – Prenatal parental counselling and 'high risk screening' important Prenatal diagnosis primarily reliant upon ultrasound detection What does this study add? Introduces a novel, lethal fetal form of cap myopathy. Evaluates range of ultrasound features and how detection can be facilitated Reconfirms fetal‐onset CM represents important, complex diagnostic challenge.